Financial Stability Report: Lessons From the Central Banks - Zakaria, Firano; Fatine, Filali Adib (Archives of Business Research, 2016)
The economic and social costs of the financial crises are very high led the central banks to register financial stability, in addition to the price stability, in the middle of their concerns. Nevertheless, the objectives of the central banks as regards financial stability are less clear and specific that in the monetary field. This difficulty related to the abstract character and multidimensional of the concept of financial stability makes difficult to quantify an objective, to check the realization of it and complicates the communication strategy to be adopted on the matter. In spite of these difficulties, the central banks reinforced their communications as regards financial stability by the publication of Financial Stability Report (FSR). The latter describe the various risks overall weighing on the stability of the financial system and formulate a judgment on its impact strength and its capacity to reabsorb the various potential shocks. The RSF aim reinforcing the transparency on the various components of the financial system and at supporting the emergence of a framework of co-operation between the various speakers. Vis-a-Vis the stakes of financial stability, the majority of the central banks widened their missions with the maintenance of financial stability. In the same way, they recorded signification advances in the installation of the framework of financial stability (institutional, lawful, and operational). Within this framework, this paper tries to describe the practices of the central banks as regards development of the FSR and formula of the recommendations aiming at proposing an exhaustive analysis of the FSR. Initially, it presents the objectives sought through this communication strategy and examines, without going into the details, the structure adopted in the development of the RSF.